Venous Thromboembolism in Patients with High-Grade Glioma - Cote, David J.; Dawood, Hassan Y.; Smith, Timothy R. (Seminars in Thrombosis and Hemostasis, 2016)
Venous thromboembolism (VTE), incorporating both deep vein thrombosis and pulmonary embolism, is a common, morbid, and potentially fatal condition. Patients undergoing surgery are at increased risk of VTE due to many perioperative factors, and patients undergoing surgery for high-grade glioma (HGG) have been found to be at an even higher risk than general surgical patients. Chemical prophylaxis of VTE during the postneurosurgical period remains one of the major dilemmas in modern neurosurgical practice due to a potential increased risk of devastating intracranial hemorrhage in the setting of anticoagulation. In this review, we aim to summarize the prevalence of VTE in patients with HGG and discuss relevant risk factors for the development of VTE after surgery for this malignancy. We also review options for VTE prophylaxis in the postoperative period and discuss appropriate management of these complex patients.
Keywords: neurosurgery; VTE; craniotomy; high-grade glioma